THE ROLE OF A VARIATIVE APPROACH IN THE DEVELOPMENT OF PROFESSIONAL COMPETENCES OF A FUTURE FOREIGN LANGUAGE TEACHER (Universal International Scientific Journal, 2026)
In this thesis, the author deeply analyzed the role, aspects and significance of the main ideas of the variational approach in the development of methodological readiness and professional competencies of future foreign language teachers. The main aspects of the variational approach were identified and widely covered as individualization of education, the use of various methods and technologies, the introduction of active teaching methods such as project methodology, case method, game technologies and information and communication technologies to promote deeper mastery of the material and the development of critical thinking, and the development of professional competence. These and other aspects such as student orientation, flexibility and individualization were analyzed as important for the effective implementation of the variational approach and improving the quality of education.
Keywords: variational approach; professional competence; foreign language